Jogja in A Pocket: An Annotated Translation - Humardhiana, Ana (STIT Buntet Pesantren Cirebon, 2022)
Jogja in A Pocket is a book dedicated to foreigners who are visiting Jogja, will visit Jogja in the near future, and/or to anyone who is fascinated with Jogja. It is a bilingual book, written in English and Indonesian. The process of making this book includes a translation process from Indonesian language to English language. This research is an annotated translation in which the researcher as the translator provides detailed explanation to account for her selection of translation equivalents. It also attempts to elaborate the process, particularly the techniques, and the challenges the translator of the book faced during the process stage. The findings show that the process was not very easy since the source texts contained Javanese specific concepts; Javanese is one of the biggest cultures in Indonesia. There were also many translation techniques from Molina and Albir (2002) applied in the process. As a book for foreigners, it is expected to be able to introduce one of the Indonesian’s cultures to world communities through its translation.